An integrated method of system maintainability, testability and supportability design and evaluation. Issue 1 (1st February 2022) - Zhang, Huazhao; Liu, Baoding; Yu, Jinsong; Liang, Guozhu
Abstract: General quality characteristics of equipment system have a guiding role for the design, production and use of equipment and are vital for the evaluation of these characteristics. They are important indicators to measure whether the equipment meets the established standard. Aiming at the problem that the design and evaluation process of equipment general quality characteristics are independent and unrelated, this paper proposes an integrated and continuous maintainability, testability and supportability design and evaluation process based on FMECA and MSFG, and designs corresponding evaluation parameters. An impact-based fault mode rating method is also proposed to better evaluate the general quality characteristics of equipment.